Quality Management Principles and Their Association With Student Satisfaction in Clinical Teaching Effectiveness in Nursing Colleges - Kanokwan, Silpakampises (2003)
A study of the application of quality management principles (QMPs) in clinical teaching and the effects on student satisfaction in teaching effectiveness is perceived while participation in the clinical experience component of the four-year and two-year continuing Bachelor of Nursing Science program at the Boromarajajonnai Colleges of Nursing in Southern Thailand. Reviews of literature show controversies in the implementation of TQM, particularly in the educational context. Past studies have focused on the classroom and the results show positive impacts. Certain QMPs, especially Student Focus, have not been fully accepted by the teachers. People Involvement in clinical teaching is also not fully cooperated. QMPs have not been applied in the dynamic environment of clinical teaching. The present study is a survey research utilizing questionnaire as an instrument for data collection from 370 final year students. Test for construct validity of the instrument has been analyzed by the Factor Analysis. Due to missing data, the final sample size is reduced to 365. This study is then focused on the use of QMPs in the dynamic environment of clinical practicum. Student Focus, Continuous Improvement, Factual Approach to Decision Making, and People Involvement are the independent QMP variables approached in this study. Dependent variables in this study are Student Satisfaction in Technical Quality and Functional Quality. The study revealed that all QMP factors were perceived by students as in the “quite high” level. This may reflect the nursing instructors’ rather good performance on the QMP factors in clinical teaching. From the descriptive analyses of dependent variables, nursing students’ perceptions of Technical Quality and Function Quality are at the “high” and “quite high” level, respectively. The correlation analysis reveals a correlation between the independent QMP variables i.e. Student Focus, Continuous Improvement, People Involvement, and Factual approach to Decision Making and Student Satisfaction in Technical Quality and Functional Quality. The regression analysis shows a significantly positive relationship between the independent variables (i.e. Continuous Improvement, People Participation, Factual Approach to Decision Making) and dependent variables (i.e. Student Satisfaction in Technical Quality and Functional quality). However, there is no significant relationship between Student focus and Student Satisfaction in Technical and Functional Quality. Therefore, there is a need for further study in order to arrive at the answer to the question as to why this factor has not been fully applied by the teachers. It is possible that certain hidden factors besides the four QMP principles discussed earlier may have an effect on student satisfaction in clinical teaching effectiveness. These factors should be studied further in order to make an on-going improvement in quality clinical teaching, with the aim to improve student learning and quality teaching, thus reflecting the efforts for securing the good practices of clinical instructors in the era of quality improvement.